"Ein poetischer Schleier": Bildung and Failed Conversion in Fanny Lewald's Jenny (1843). (15th August 2020) - Greenberg, Lea H.
Abstract : This article analyzes the intersection of literature and Christian‐Jewish love in Lewald's 1843 novel Jenny, where Bildung is both a medium to transcend the constraints of Jewish identity and a force reinscribing these constraints. Literature is the space in which the novel's protagonist, Jenny, falls for her Christian tutor and pursues conversion. In order to reconcile her secular worldview with the spiritual demands of conversion, Jenny attempts to encode Christian doctrine into a system of understanding shaped by her literary imagination and engagement with Bildung . This strategy fails, ending her romance and reinforcing an identification with her father. Bildung, which in part propelled German Jews into the middle class, ultimately prevents Jenny from escaping her status as a Jewish woman. The Jewish daughter's secular education in conjunction with her romantic rebellion away from the Jewish family stages the limitations of—and anxieties toward—refashioning Jewish identity in the non‐Jewish world.